Life cycle assessment of reusable plastic food packaging - Yadav, Pooja; Silvenius, Frans; Katajajuuri, Juha-Matti; Leinonen, Ilkka (Elsevier, 2024)
The present study focuses on the cradle-to-grave life cycle assessment (LCA) of a reusable takeaway food container. The system boundary includes the production, transport, use, and end of life (EoL) stages of container, considering recycling and incineration, including all the inputs (material and energy) and outputs (emissions). Scenarios (10, 30, and 100 uses of a reusable container with EoL) were proposed and compared with a single-use container. The primary data was collected from industry and secondary data was taken from the literature and the Ecoienven 3.9.1 database. The functional unit (FU) was “one use of a container”, and the ReCiPe 2016 Midpoint (H) method was used. The results showed that with a centralised collection and washing system, the global warming potential (GWP) for a single-use container (0.020 kg CO2 eq./FU) per FU had higher GWP than 10 uses (0.015 kg CO2 eq./FU), 30 uses and 100 uses (0.007 kg CO2 eq./FU) of the reusable container (EoL recycling). The GWP of a single-use container is 1.3 times higher than 10 uses of the container which results in a minimum six uses of the reusable container, providing a benefit over single-use container (EoL recycling). In EoL incineration, 10 uses scenario led to a decrease in the GWP of 46%, while 100 uses resulted in a significant reduction in the GWP of 83% compared to single-use per FU. It was found that the efficiency of the return system for empty containers significantly influenced the results. This study also quantified potential plastic waste for various scenarios.
Keywords: environmental impact; life cycle analysis; recycling; incineration; single-use plastic food packaging; reusable plastic food packaging